If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -2) = -4x + 14 Reorder the terms: -2(-2 + x) = -4x + 14 (-2 * -2 + x * -2) = -4x + 14 (4 + -2x) = -4x + 14 Reorder the terms: 4 + -2x = 14 + -4x Solving 4 + -2x = 14 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 4 + -2x + 4x = 14 + -4x + 4x Combine like terms: -2x + 4x = 2x 4 + 2x = 14 + -4x + 4x Combine like terms: -4x + 4x = 0 4 + 2x = 14 + 0 4 + 2x = 14 Add '-4' to each side of the equation. 4 + -4 + 2x = 14 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 14 + -4 2x = 14 + -4 Combine like terms: 14 + -4 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| -5-(-5/2) | | 33x-2+12x+2=180 | | -5/2-(-5/4) | | 33x-2+12+2=180 | | -75-11x=46 | | 6v-4=-2(v-2) | | 8/5k-3/2k= | | K/12-1=-3 | | x^3/x^6 | | c=1075 | | (64x^5y^-4z^9)^-2/3 | | 12x+102=-66 | | 3+(2d-5)=2+(2d-4) | | (2lnx-(lnx)^2)/x | | 416/13 | | X^2-2+4x^2=18 | | 28=4x+8(x-7) | | (b*2.8)+83=39 | | 7=54.85-0.75x | | -4x-[-(7x)+2]=-14 | | 6+3(11)-(25)= | | x+3.5x=0.5+x | | 3(u+4)+4u=-2 | | -3(3w-3)=10(7-w) | | X/8=3/17 | | p-9r+3p+3r= | | 15x^2=18x | | 5z+7=5(z+4)-20 | | .666666666666666666b+5=20-b | | 6(1-4n)+8(n-2)= | | 2x-4+1=-2x+1 | | 81=n-100 |